Maqasid Sharia As A Philosophical Foundation In Islamic Economic Policy Making - Arum, Hafidza Sanshia; Rupita, Nanda Ega; Syahpawi; Muhammad Albahi (MALIA: Jurnal Ekonomi Islam, 2024)
Introduction: The application of Sharia economics often focuses on aspects of formal legality, ignoring the social and desire dimensions. This challenge makes the Sharia principles less optimal for creating benefits. Globalisation adds pressure to innovation, but Maqasid Sharia offers a holistic framework for material and spiritual balance. Methods: Using the literature study method, this study examines the theory and application of Maqasid Sharia which includes the protection of religion, soul, intellect, heredity, and property in economic policy Results: The results show that, although Maqasid Syariah provides a comprehensive framework, the main challenges in its implementation are an overly legalistic approach and a lack of innovation in Islamic financial products. Conclusion and suggestion: Maqasid Syariah as the foundation of syariah economy provides strategic guidance for fair, inclusive, and sustainable policies with Five main elements: religion, soul, intellect, heredity, and wealth. Despite being able to address global challenges such as social inequality and climate change, its implementation faces obstacles such as the dominance of a legalistic approach, lack of innovation, and lack of regulation and infrastructure. Recommendations include the integration of Maqasid values in policy, strengthening regulation, developing Sharia financial technology, redistribution of wealth through zakat and waqf, and innovative products such as green sukuk. The synergy between government, private, and historians is necessary for effective implementation.